Acute Renal Injury in Patients with ARDS: Presence and Associated Factors: Same as above - Shahzadi, Sumbul; Siddiqi, Fuad Ahmad; Khan, Imran; Siddiqi, Kanaz Ahmad; Ejaz, Amen; Cheema, Ayesha Ashraf (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the occurrence of Acute Renal Injury in Acute Respiratory Distress Syndrome patients along with contribution of co-morbidities and risk factors for the development of AKI. Study Design: Comparative Cross Sectional study. Place and Duration of Study: This study was done at medical ICU, Department of Medicine, Combined Military Hospital (CMH), Rawalpindi from Jan 2023 to Oct 2023. Methodology: A total of 68 patients, with confirmed ARDS, 18yrs or above were included. The presence of co-morbidities in all patients was recorded. Patients BMI and SOFA score were calculated. Patients were divided as Group 1 (those who develop AKI) and Group 2 (those who did not develop AKI). On the basis of serum creatinine level group 1 patients were further categorized into three groups: stage I AKI, stage II AKI, and stage III AKI. The median (IQR) was calculated for non-normal variables. Chi-square test, unpaired t-test, and Mann-Whitney U test were applied and p≤0.05 was taken as statistically significant. Results: Acute Kidney Injury was observed in 39(57.4%) patients (Group 1) while 29(42.6%) patients did not develop any AKI (Group 2). Group 1, had a significantly higher BMI, SOFA score, Comorbidities like Diabetes Mellitus (DM), Malignancies and liver Disease. Non-pulmonary sepsis was high in Group 2. There was a statistically significant association between AKI stages and specific characteristics. Conclusion: AKI was quite common among ARDS individual. A Higher BMI, SOFA score, presence of DM, active malignancy, liver and cardiac illness showed strong association with the development of AKI.